Magnetic Resonance Colonography Including Diffusion-Weighted Imaging in Children and Adolescents With Inflammatory Bowel Disease. Issue 1 (January 2015) - Sirin, Selma; Kathemann, Simone; Schweiger, Bernd; Hahnemann, Maria L.; Forsting, Michael; Lauenstein, Thomas C.; Kinner, Sonja
<x xml:space="preserve">Abstract</x> Objectives Magnetic resonance colonography (MRC) is a well-accepted, noninvasive imaging modality for the depiction of inflammatory bowel disease. Diffusion-weighted imaging (DWI) is very helpful to display inflammatory lesions. The aim of this retrospective study was to assess whether intravenous contrast is needed to depict inflammatory lesions in bowel magnetic resonance imaging if DWI is available. Materials and Methods Thirty-seven patients (23 females, 14 males; mean age, 14.6 years) underwent MRC on a 1.5-T scanner (MAGNETOM Avanto; Siemens). Contrast-enhanced T1-weighted (ce-T1-w) sequences and DWI sequences in axial and coronal planes (b = 50, 500, 1000) were acquired. Two reviewers evaluated (1) DWI, (2) ce-T1-w MRC, as well as (3) DWI and ce-T1-w MRC concerning lesion conspicuity. The preferred b value was assessed. Colonoscopy was performed within 1 week, including biopsies serving as the reference standard. Sensitivities and specificities were calculated, and interobserver variability was assessed. Results Mean sensitivity and specificity of the 2 readers for the depiction of inflammatory lesions were 78.4%/100% using ce-T1-w MRC, 95.2%/100% using DWI, and 93.5%/100% combining both imaging techniques compared with colonoscopy including results of the histopathological samples. In 6 patients, inflammatory lesions were only detected by DWI; in another 6 patients, DWI detected additional lesions. The κ values for the 2 readers were excellent (k = 0.92–0.96). The preferred b value with the best detectability of the lesion was b1000 in 28 of the 30 patients (93.3%) with restricted diffusion. Conclusions Diffusion-weighted imaging of the bowel identified inflammatory lesions with high accuracy and revealed lesions that were not detectable with ce-T1-w imaging alone. A b value of 1000 showed the best lesion detectability.